EFFECT OF THIOREDOXIN FUSION AND MALTOSE BINDING PROTEIN FUSION ON PROTEIN X HEPATITIS B VIRUS SOLUBILITY IN Escherichia coli - Dira Surti, Amira
The Hepatitis B virus X protein (HBx) have an important role in the pathogenesis of hepatocarcinoma caused by Hepatitis B virus infection. HBx structure with 9 cysteine residues and 4 disulfide bonds caused HBx production in Escherichia coli as inclusion bodies and inactive. Interaction study of p53 with inactive HBx will not correctly reveal the detail of interaction, in relation to hepatocellular carcinoma. The aim of this study was to increase the solubility of HBx protein in E. coli with thioredoxin (Trx) and Maltose Binding Protein (MBP) fusion. Trx and MBP at Nterminal were fused with HBx at C-terminal (Trx-HBx and MBP-HBx). Overproduction of protein was optimized in various concentrations of IPTG (0.1 mM and 0.5 mM IPTG), various induction temperature (17°C, 25°C, and 37°C), and various induction time (4, 8, and 16 hours). MBP-HBx protein was overproduced using E. coli BL21 (DE3), while the Trx-HBx protein was overproduced using E. coli BL21 (DE3) and E. coli Rosetta-gami. High amounts of Trx-HBx and MBP-HBx were produced in E. coli BL21 (DE3) at noninduced conditions. Overproduction of high amounts of Trx-HBx in E. coli Rosetta-gami was obtained at a concentration of 0.1 mM IPTG. Variations in the three induction temperatures showed that Trx-HBx and MBP-HBx were produced as inclusion bodies, so induction temperature of 17°C and 25°C was chosen to overproduce Trx- HBx in E. coli Rosetta-gami. The highest amount of 39.3% soluble Trx-HBx was obtained in overproduction with induction of 0.1 mM IPTG, temperature 17°C, for 8 hours in E. coli Rosetta-gami.